2022
DOI: 10.1001/jamapediatrics.2022.0056
|View full text |Cite|
|
Sign up to set email alerts
|

Five-Year Trends in US Children’s Health and Well-being, 2016-2020

Abstract: Ensuring the well-being of the 73 million children in the United States is critical for improving the nation's health and influencing children's long-term outcomes as they grow into adults. OBJECTIVE To examine recent trends in children's health-related measures, including significant changes between 2019 and 2020 that might be attributed to the COVID-19 pandemic. DESIGN, SETTING, AND PARTICIPANTS Annual data were examined from the National Survey of Children's Health (2016-2020), a population-based, nationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
93
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(99 citation statements)
references
References 23 publications
2
93
0
4
Order By: Relevance
“…Previous work has shown that preventive medical visits (not including vision screening) decreased significantly from 2019 to 2020. 6 Our findings align with this observation and suggest that decreases extended to vision-related access. Future research should explore the impact of health insurance status on vision care access and need among children in the United States across the same time period.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Previous work has shown that preventive medical visits (not including vision screening) decreased significantly from 2019 to 2020. 6 Our findings align with this observation and suggest that decreases extended to vision-related access. Future research should explore the impact of health insurance status on vision care access and need among children in the United States across the same time period.…”
supporting
confidence: 89%
“…The 2020 National Survey of Children's Health (NSCH) provides an opportunity to study 5-year trends in childhood vision metrics, including the potential impacts of the SARS-CoV-2 pandemic. 6 The purpose of this study is to examine recent trends in vision screening, vision specialist utilization, reported blindness, and unmet access in vision care, including specific pre-pandemic and post-pandemic changes.…”
mentioning
confidence: 99%
“…However, prior studies have shown between 2016-2020, there were significant increases in children's diagnosed depression and anxiety, although after onset of the COVID-19 pandemic specifically, there were significant year-over-year increases in children's diagnosed behavioral or conduct issues, supporting our conclusions that the increase in MH-visits is attributable to factors related to the pandemic. 19 …”
Section: Limitationsmentioning
confidence: 99%
“…However, prior studies have shown between 2016-2020, there were significant increases in children's diagnosed depression and anxiety, although after onset of the COVID-19 pandemic specifically, there were significant year-over-year increases in children's diagnosed behavioral or conduct issues, supporting our conclusions that the increase in MH-visits is attributable to factors related to the pandemic. 19 Our study was also limited to schools geographically where in-person learning was available, and did not include children seeking MH-services from providers other than school-nurses, such as school counselors, other school-based MH-providers, or MH-providers outside of school, which may limit the generalizability of our findings. Given the nature of school-nurse services, it is likely the same students may be visiting the school-nurse for MH-related symptoms on more than one occasion; given we did not have access to individual level data to examine this, our analyses used school-nurse visits as observations.…”
Section: Limitationsmentioning
confidence: 99%
“…Two recent publications on child mental health illustrate this shift. One is a study that trended 5 years of youth mental health data from the National Survey of Children's Health (Lebrun-Harris et al, 2022). The results included survey response entered over the years for some 175,000 children ages birth to 17 years.…”
mentioning
confidence: 99%